2018
DOI: 10.1111/dme.13873
|View full text |Cite
|
Sign up to set email alerts
|

Prospective memory slips are associated with forgetting to take glucose‐lowering therapies among adults with diabetes: results from the second Diabetes MILES – Australia (MILES‐2) survey

Abstract: Aims Prospective memory has been long considered a fundamental cognitive ability for optimal medication taking, but the role of prospective memory errors (termed 'slips') in diabetes self-care is unclear. Our aim was to examine associations between prospective memory and medication taking in adults with Type 1 and Type 2 diabetes mellitus.Methods Some 901 adults with Type 1 diabetes and 927 with Type 2 diabetes completed a cross-sectional survey focused on the psychological and behavioural aspects of living wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The total number of study visits (inperson, e-mail, and phone) for HCL participants was greater than for the control group (median [interquartile range (IQR)] 31 [23,38] vs. 19 [15,24] visits; P , 0.001) as was time spent with HCL participants for study activities, education, and review of pump settings compared with control participants (27 [21,32] vs. 14 [11,19] hours; P , 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total number of study visits (inperson, e-mail, and phone) for HCL participants was greater than for the control group (median [interquartile range (IQR)] 31 [23,38] vs. 19 [15,24] visits; P , 0.001) as was time spent with HCL participants for study activities, education, and review of pump settings compared with control participants (27 [21,32] vs. 14 [11,19] hours; P , 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that, as with the diabetes burden and treatment satisfaction measures, subjective sleep benefits were masked by sleep disruption from HCL therapy (31). The absence of any detectable increase in self-perceived memory failures among those managing HCL is encouraging, as these have been previously linked to forgetting medication among adults with type 1 diabetes (32). It is possible that longer studies, resulting in greater familiarity with HCL technology, could still result in improvements in the nonglycemic parameters discussed above.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have demonstrated the relationship between poor PM and medication nonadherence. 7,8 Laboratory research has shown that performance on a PM task was correlated with medication adherence in diabetic participants. 9 Improving PM could be a means to enhance medication adherence within this population.…”
Section: Introductionmentioning
confidence: 99%